Assessment of mechanical weeders in paddy fields: A study on operational effectiveness in Bangladesh - Subrata Paul; Bidhan Chandra Nath; Md. Durrul Huda; Md. Golam Kibria Bhuiyan; Haimonti Paul (Heliyon)
Rice is a vital crop for food security in Bangladesh, occupying 75 % of its agricultural land. Weed management is crucial for maintaining rice yields because weeds compete for nutrients, water, and space, leading to yield losses ranging from 15 % to 60 %. Traditional hand weeding is labor-intensive and costly, driving the need for efficient, sustainable alternatives. This study assessed the operational effectiveness of five weeding technologies: BRRI Power Weeder (PW), BRRI Weeder (BW), BRRI Conical Weeder (CW), BRRI Double Row Weeder (DW), and Manual Hand Weeding (HW). Field trials were conducted at the Bangladesh Rice Research Institute (BRRI) and farmers' fields in Jogitola, Gazipur, during the 2022 Boro season. A comprehensive assessment of five distinct weeding technologies for rice cultivation in Bangladesh, considering their operational performance under research and field conditions. Essential performance indicators were evaluated-field capacity, weeding efficiency, tiller damage, and fuel consumption. The results revealed that the BRRI Power Weeder had the highest field capacity (669 m2/h) but caused more crop damage and had lower field efficiency due to turning delays. In contrast, manually operated weeders like BW and CW showed moderate field capacities (247 m2/h and 228 m2/h, respectively) with better crop safety and higher field efficiency. Manual hand weeding, while labor-intensive with the lowest field capacity (100 m2/h), caused minimal tiller damage and was most effective for small-scale fields. The findings indicate that mechanical weeders offer labor savings and improved efficiency, but crop safety and field conditions must guide technology selection. The commitment to balancing operational efficiency with crop safety is crucial for sustainable rice production in Bangladesh.